ANALISIS KARAKTER ADIT SEBAGAI ROLE MODEL SISWA SEKOLAH DASAR PADA FILM ANIMASI ADIT & SOPO JARWO - Aida Syahira; Mutiara Pasca; Putri Desmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The proliferation of imported animated shows that lack educational value, coupled with the limited number of local animated characters portrayed as role models, underscores the need for an in-depth study of characters in Indonesian animated series. This study aims to analyze the character of Adit as a role model for elementary school students in the animated film Adit & Sopo Jarwo. This study employs a qualitative approach using content analysis. Data were collected through observation of dialogue, behavior, and interactions among characters across six episodes from the official MD Animation YouTube channel. Data analysis followed the interactive model by Miles & Huberman through three stages: data reduction, data presentation, and drawing conclusions. The research results indicate that there are 9 positive character traits consistently displayed by the character Adit, including helping others, cooperation, leadership, courage to try new things, admitting mistakes, enthusiasm for learning, responsibility, perseverance, and trustworthiness.These values are conveyed through a simple storyline that is close to children’s daily lives, making them easy to understand, internalize, and emulate. Thus, the animated film Adit & Sopo Jarwo is worthy of recommendation to educators and parents as an effective character education learning medium for elementary school students.